Optimizing planting geometries in eucalyptus-based food production systems for enhanced yield and carbon sequestration - S. B. Chavan; S. B. Chavan; R. S. Dhillon; Chhavi Sirohi; Ibrahim A. Saleh; A. R. Uthappa; A. Keerthika; Dinesh Jinger; Hanamant M. Halli; Aliza Pradhan; Vijaysinha Kakade; Amrut Morade; et al. (Frontiers in Sustainable Food Systems, 2024)
The integration of trees into diverse land-use systems holds potential for India to meet nationally determined contribution (NDC) targets under the Paris Climate Agreement. With a target of sequestering 2.5–3 billion tons of CO2 equivalent by 2030, the study focused on the widespread and economically viable eucalyptus-based agroforestry, practiced widely in various planting geometries tailored to meet industrial end-use requirements. In this context, a detailed study was conducted to quantify the influence of five planting geometries [3 m × 3 m, 6 × 1.5 m, 17 × 1 × 1 m (paired row) and two boundary plantations (east–west and north–south directions) at 2 m away from tree to tree] of eucalyptus on intercrops [dhaincha (Sesbania aculeata)—barley (Hordeum vulgare L.) rotation] biomass, soil properties, and carbon stock of the system during 2009–2016. Results revealed that biomass accumulation of different tree components was 62.50%–74.09% in stem; 6.59%–9.14% in branch; 3.18%–5.73% in leaves; 12.20%–20.44% in stump roots; and 1.71%–3.48% in fine roots across the planting geometries. The mean carbon content of the stem, branch, leaves, and roots was 49.00, 47.00, 43.00, and 49.00%, respectively. Over the 8-year period, geometry of 3 × 3 m performed better in terms of total biomass production (344.60 Mg ha− 1 by tree biomass and 62.53 Mg ha−1 by intercrops). The independent parameter, DBH2H (DBH: diameter at breast height and H: tree height), was found to be a very good predictor of dry weight, followed by DBH alone. Among various functions (linear, allometric, logistic, Gompertz, Chapman, and exponential), the best-fit equation was allometric, i.e., B = 300.96 × DBH2H0.93 (adjusted R2 = 0.96) for eucalyptus based on universal model adequacy and validation criteria. The carbon sequestration rate was maximum (20.79 Mg C ha−1 year−1) in 3 × 3 m followed by 17 × 1 × 1 m. The total carbon stock of eucalyptus-based system (tree + crop + soil) varied significantly under different planting geometries and sole crop rotation (dhaincha–barley). The higher carbon stock (237.27 Mg ha−1) was obtained from 3 × 3 m spacing and further partitioning carbon stock in trees—166.29 Mg ha−1, crops—25.01 Mg ha−1 and soil—45.97 Mg ha−1. The paired row spacing (17 × 1 × 1 m) yielded higher crop yield and net returns (Rs. 600,475 ha−1), underscoring wide spacing’s role in system productivity and sustainability. Tree-based systems were valuable components of agriculture, advocating for their widespread adoption to reduce CO2 emissions and generate income through carbon credits. These findings will provide crucial insights into sustainable land-use practices and advance India’s commitment toward adaptation of climate change mitigation strategies.